Etika Guru Dalam Pemberdayaan Pembelajaran - Munir, Munir (MADINAH, 2015)
There is still a presumption in the community that anyone can teach so as not to feel the need to deepen the science of teaching. This is true for those who can teach by themselves without studying it, but not infrequently individuals who can not teach but because of one another is required to teach. In addition, teachers do not care whether learners can understand what is taught or not. The goal of self learning can be achieved or not. Such things can not be categorized in teaching or professional teaching. Teaching is always related to the goal to be achieved, then teaching must be accountable. Therefore, to conduct learning activities required a benchmark or guidance in the implementation so that it can be assessed and accountable. Through these guidelines teachers can find out how to teach what they should.